MERANCANG SEJARAH YANG MULTIKULTURALIS DALAM KURIKULUM 2004 - Hermanu Joebagio (LPMPP Universitas Negeri Yogyakarta, 2005)
AbstractAfter the crisis of 1998, which was followed by a periode labeled as reformasi, Indonesia having entered a transitional phase from authoritarianrule toward a new democratic system. In transitional phase emerged outbursts of ethnic and religious violences in various regions of the archipelago.This articles tries to analyze multicultural studies in a period of the new order. In education perspective, the outbursts of ethnic and religious violences after reformasi, showed that the new order was failure to make harmony by created the instruction of religious, civic skill, and military instructional as labeled kewiraan. Recently time, history, could be formulated to be multicultural studies. The curriculum of historyhave been modified and transformed to the multicultural studies by used the burhani technical system. The burhani technical system usually used to analyze religious texts. The themes of curriculum history, and then modify, to produce the themes of multicultural studies by consider the social sciences (sociology, politics, and economics) and humanity sciences (anthropology and religion).Key words: authoritarian, democratic, violence, multicultural studies, and burhani technical system